Multiple Positive Solutions for a Coupled System of p-Laplacian Fractional Order Two-Point Boundary Value Problems - K. R. Prasad; B. M. B. Krushna (International Journal of Differential Equations)
This paper establishes the existence of at least three positive solutions for a coupled system of p-Laplacian fractional order two-point boundary value problems, D0+β1(ϕp(D0+α1u(t)))=f1(t,u(t),v(t)), t∈(0,1), D0+β2(ϕp(D0+α2v(t)))=f2(t,u(t),v(t)), t∈(0,1), u(0)=D0+q1u(0)=0, γu(1)+δD0+q2u(1)=0, D0+α1u(0)=D0+α1u(1)=0, v(0)=D0+q1v(0)=0, γv(1)+δD0+q2v(1)=0, D0+α2v(0)=D0+α2v(1)=0, by applying five functionals fixed point theorem.